Holland op zijn hoogst (Bulletin KNOB, 1990)
The hereafter following has been pronounced on the symposium 'Holland at its Highest' organized by the Section Architecture and Town-planning of the Royal Antiquarian Society of the Netherlands. 'As you all know the title of this symposium is a paraphrase on the title of one of the most legendary publications from the Dutch history of art: 'Holland and its Narrowest'. The author Victor Eugène Louis de Stuers not only was a historian of art and publicist but also a caricaturist. Denouncing the decay and neglect of Dutch monuments in 1873 he described both municipality and church government as 'boundless vandals' responsible for the 'corrosive cancer' with which he meant the decay of our cultural heritage. The major part of the people consisted of culture barbarians, whose daily reading-matter was the stock-exchange quotation besides cancelling every service of each budget which did not end with a credit balance. Thus 'Holland at its Narrowest' is one great caricature and one great accusation at the same time.Before l re-read De Stuers' article in view of to-day, in view of 'Holland at its Highest', l swore to myself not to use this article to show that some parts of this phenomenal discourse still are valid to-day. However, the Dutch cultural climate still is being controlled by the tangible reality of credit balance. One of the reasons for De Stuers flaming accusation, the care for the individual monument, largely has been solved. The pursuit of the credit balance is the real threat of our cultural heritage. This pursuit is being dominated by the prey full of golden eggs, the 'top-location'. The top-location is the phantom of our fin-du- siècle. Architecture and town-planning respond to fluctuation in prices just like a mammoth tanker. With endless delay. The profession of town-planning actually does not exist anymore in our country. Art, culture, the instinct of the beautiful and the sublime, the acknowledgement of the moral and humanitarian benefit, also words of De Stuers, these abstract sensitive characteristics which provide architecture and town-planning with real value do not matter anymore.The contemporary conception of architecture and town-planning misses the cultural component and consequently the historical continuity which is part of that cultural component. Architecture and town-planning have been subordinated to the credit balance, to politics and to bureaucracy. The predominating anonymous design-culture of aluminium and plate-glass does not deserve the name of architecture anymore but every municipality yields to this 'architecture' longing to be taken for modern and economically prosperous. This architecture does not care about the past, the urban context, let alone eternity. Victor de Stuers' recommendations to the at the time reigning government are still valid today. This vandalism has to be restrained by the authorities and the entire nation.